Merkel cell carcinoma: updates in tumor biology, emerging therapies, and preclinical models - Pedersen, Elisabeth A.; Verhaegen, Monique E.; Joseph, Mallory K.; Harms, Kelly L.; Harms, Paul W. (Frontiers in Oncology, 2024)
Merkel cell carcinoma (MCC) is an aggressive cutaneous neuroendocrine carcinoma thought to arise via either viral (Merkel cell polyomavirus) or ultraviolet-associated pathways. Surgery and radiotherapy have historically been mainstays of management, and immunotherapy has improved outcomes for advanced disease.However, there remains a lack of effective therapy for those patients who fail to respond to these established approaches, underscoring a critical need to better understand MCC biology for more effective prognosis and treatment. Here, we review the fundamental aspects of MCC biology and the recent advances which have had profound impact on management. The first genetically-engineered mouse models for MCC tumorigenesis provide opportunities to understand the potential MCC cell of origin and may prove useful for preclinical investigation of novel therapeutics. The MCC cell of origin debate has also been advanced by recent observations of MCC arising in association with a clonally related hair follicle tumor or squamous cell carcinoma in situ. These studies also suggested a role for epigenetics in the origin of MCC, highlighting a potential utility for this therapeutic avenue in MCC. These and other therapeutic targets form the basis for a wealth of ongoing clinical trials to improve MCC management. Here, we review these recent advances in the context of the existing literature and implications for future investigations.